Composition for resist underlayer film formation, pattern forming method, and method for forming resist underlayer film

CN122962887APending Publication Date: 2026-10-23SHIN ETSU CHEMICAL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202610521164.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-22
Filing Date
2026-04-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但是,这些材料的课题为在含有溶解性低的有机磺酰基阴离子的树脂的析出所致的低保存稳定性、来自不充分的膜固化性所致的互混的残渣

Benefits of technology

[0099]如以上说明,本发明提供防止长期保存时的析出且具有良好的保存稳定性的抗蚀剂下层膜形成用组成物。此抗蚀剂下层膜形成用组成物能维持抗蚀剂图案的密合性同时去除抗蚀剂底部的残渣,故在要求形成非常微细的图案的步骤中极为有用。又,若为本发明的抗蚀剂下层膜的形成方法,则能在被加工基板上充分固化,也能防止来自互混的抗蚀剂的残渣。尤其,在半导体装置制造步骤中由多层抗蚀剂法所进行的微细图案化制程为有用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962887A_ABST
    Figure CN122962887A_ABST
Patent Text Reader

Abstract

The present invention relates to a composition for resist underlayer film formation, a pattern forming method, and a method for forming a resist underlayer film. The present invention provides a composition for resist underlayer film formation which provides a resist underlayer film having good storage stability, good pattern collapse inhibiting properties, and removal ability of resist residue at the bottom of a pattern; a pattern forming method using the aforementioned composition; and a method for forming the aforementioned resist underlayer film using the aforementioned composition. A composition for resist underlayer film formation comprising: (A) a high molecular compound comprising a structural unit containing an organic sulfonyl anion structure and a structure of onium cation from a sulfur atom, and the aforementioned structure of onium cation is bonded to the polymer main chain in a pendant manner; (B) a thermal acid generator; and (C) an organic solvent, and the aforementioned (A) high molecular compound and the aforementioned (B) thermal acid generator have the same organic sulfonyl anion molecule.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composition for forming a photoresist underlayer film, a pattern forming method using the composition for forming a photoresist underlayer film, and a method for forming a photoresist underlayer film using the aforementioned composition for forming a photoresist underlayer film. Background Technology

[0002] With the increasing integration and speed of LSI (Lithium-ion Sensor), the miniaturization of pattern sizes is progressing rapidly. Photolithography, with this miniaturization, achieves the formation of fine patterns through the shortening of light source wavelengths and the appropriate selection of corresponding resist compositions. At its core is the use of a single-layer positive photoresist composition. This single-layer positive photoresist composition possesses a framework within the resist resin that is etch-resistant to dry etching by chlorine-based or fluorine-based gas plasmas. It also has a resist mechanism that allows the exposed area to dissolve, forming a pattern. The remaining resist pattern then serves as an etching mask for dry etching of the substrate coated with the photoresist composition.

[0003] However, directly reducing the thickness of the photoresist film, i.e., further shrinking the pattern width, will decrease the resolution of the photoresist film. Furthermore, if the photoresist film is to be patterned using a developer, the aspect ratio will become too large, resulting in pattern corruption. Therefore, with miniaturization, the thickness of the photoresist film has gradually become thinner.

[0004] On the other hand, in the processing of substrates, a patterned photoresist film is typically used as an etching mask, and the substrate is processed by dry etching. However, in reality, there is no dry etching method that can achieve complete etch selectivity between the photoresist film and the substrate. Therefore, the photoresist film is also damaged during substrate processing, and the photoresist film may even break down, making it impossible to correctly transfer the resist pattern to the substrate. Thus, with the miniaturization of patterns, higher dry etching resistance is required for the photoresist composition. Furthermore, with the shortening of exposure wavelengths, the resin used in the photoresist composition needs to have low light absorption at the exposure wavelength. Therefore, compared to changes towards i-rays, KrF, and ArF, there is a trend towards resins with phenolic varnish resins, polyhydroxystyrene, and aliphatic polycyclic skeletons. However, in reality, the etching rate under the aforementioned dry etching conditions is faster, and the most recent photoresist compositions with high resolution tend to have weaker etching resistance.

[0005] Therefore, it is necessary to dry etch the substrate with a thinner photoresist film that has weaker etching resistance. Ensuring the quality of materials and processing in this step is of paramount importance.

[0006] One method to address this problem is the multilayer photoresist method. This method involves inserting an intermediate photoresist film, which has a different etching selectivity than the photoresist film (i.e., the upper photoresist film), between the upper photoresist film and the substrate being processed. After the upper photoresist film is patterned, the pattern is used as a dry etching mask, and the pattern is transferred to the intermediate photoresist film by dry etching. The intermediate photoresist film is then used as a dry etching mask, and the pattern is transferred to the substrate being processed by dry etching.

[0007] One type of multilayer photoresist method is the three-layer photoresist method, which uses general photoresist compositions used in single-layer photoresist methods. In this three-layer photoresist method, for example, an organic film such as a phenolic varnish is formed on the substrate as the lower photoresist film, a silicon-containing film is formed on it as the silicon-containing photoresist intermediate film, and a general organic photoresist film is formed on it as the upper photoresist film. For dry etching using fluorine-based gas plasma, the organic photoresist upper film achieves good etch selectivity over the silicon-containing photoresist intermediate film; therefore, the pattern of the upper photoresist film is transferred to the silicon-containing photoresist intermediate film by dry etching using fluorine-based gas plasma. Furthermore, for etching using oxygen or hydrogen, the silicon-containing photoresist intermediate film achieves good etch selectivity over the lower photoresist film; therefore, the pattern of the silicon-containing photoresist intermediate film is transferred to the lower photoresist film by etching using oxygen or hydrogen. According to this method, even if a photoresist composition that is difficult to form a pattern with sufficient film thickness for direct processing of the substrate is used, or a photoresist composition with insufficient dry etching resistance for processing the substrate is used, as long as the pattern can be transferred to a silicon-containing film (silicon-containing photoresist intermediate film), a pattern of an organic film (photoresist lower layer film) formed by phenolic varnish or the like with sufficient dry etching resistance for processing can be obtained.

[0008] In recent years, vacuum ultraviolet (EUV) lithography with a wavelength of 13.5 nm has attracted attention as a powerful alternative to combining ArF immersion lithography with multiple exposure processes. This technology allows for the formation of fine patterns with a half-pitch of less than 25 nm in a single exposure.

[0009] On the other hand, in EUV lithography, to compensate for insufficient light source output, the resist material is required to have high sensitivity. However, with increasing sensitivity, the increase in shot noise is closely related to the increase in edge roughness (LER, LWR) of the line pattern. Therefore, achieving both high sensitivity and low edge roughness has been listed as one of the important issues in EUV lithography.

[0010] In recent years, attempts have been made to increase the sensitivity of photoresists and reduce the impact of shot noise, with the use of metallic materials in photoresist materials being explored. Compounds containing metallic elements such as barium, titanium, hafnium, zirconium, and tin exhibit higher absorbance for EUV light compared to metal-free organic materials, suggesting the potential for improved photoresist sensitivity and suppression of shot noise. Furthermore, combining metallic photoresist patterns with a substrate composed of non-metallic materials can lead to high-selectivity etching processes.

[0011] For example, resist materials containing metal salts or organometallic complexes have been explored (Patent Documents 1 and 2), and non-chemically amplified resist materials using metal oxide nanoparticles have been explored (Patent Documents 3 and 4, Non-Patent Document 1). However, the problems with these metal-containing resists are pattern collapse and the adverse effects of resist residues at the bottom of the pattern on the manufacturing process.

[0012] Therefore, a material has been reported that uses a tightly sealed film containing organic sulfonyl anions to supply acid to the bottom of the resist and promote the reaction of the resist in the exposed area, thereby inhibiting pattern collapse and resist residue (Patent Documents 5, 6, 7). However, the problems with these materials are low storage stability due to the precipitation of resins containing poorly soluble organic sulfonyl anions and mixed residues due to insufficient film curing.

[0013] Existing technical documents

[0014] Patent documents

[0015] [Patent Document 1] Japanese Patent No. 5708521

[0016] [Patent Document 2] Japanese Patent No. 5708522

[0017] [Patent Document 3] US Patent No. 9,310,684

[0018] [Patent Document 4] International Publication No. 2003 / 017002

[0019] [Patent Document 5] Japanese Patent No. 5415982

[0020] [Patent Document 6] Japanese Patent No. 7634473

[0021] [Patent Document 7] International Publication No. 2025 / 028314

[0022] Non-patent literature

[0023] [Non-Patent Literature 1] Proc. SPIE Vol.7969, 796915 (2011) Summary of the Invention

[0024] [The problem that the invention aims to solve]

[0025] The present invention was made in view of the foregoing circumstances, and its object is to provide a composition for forming a photoresist underlayer film that provides a photoresist underlayer film with good preservation stability, good pattern collapse suppression performance and the ability to remove photoresist residue at the bottom of the pattern, a pattern forming method using the aforementioned composition, and a method for forming the aforementioned photoresist underlayer film using the aforementioned composition.

[0026] [Methods for solving the problem]

[0027] To address the aforementioned issues, the present invention provides a composition for forming a resist underlayer film, comprising:

[0028] (A) A polymeric compound comprising structural units containing an organic sulfonyl anionic structure and an onium cationic structure from a sulfur atom, wherein the aforementioned onium cationic structure is dangling bonded to the polymer backbone;

[0029] (B) Thermal acid generating agent; and

[0030] (C) Organic solvents,

[0031] Furthermore, the aforementioned (A) polymeric compound and the aforementioned (B) thermal acid generating agent have the same organic sulfonyl anionic molecule.

[0032] If such a composition is used for forming the lower layer of the resist film, good film curing properties can be obtained by means of a hot acid generating agent, and the leaching of components from polymeric compounds and hot acid generating agents can be prevented during long-term storage.

[0033] Furthermore, in this invention, the structural unit containing the aforementioned organic sulfonyl anion structure and the onium cation structure from the sulfur atom contained in the aforementioned (A) polymer compound is preferably represented by the following general formula (1) or (2).

[0034] [Chemistry 1]

[0035]

[0036] (In the formula, R1 is a hydrogen atom or a methyl group, R2 is a substituted or unsubstituted divalent organic group or a single bond that may also contain ether or ester bonds, Ar1 and Ar2 are substituted or unsubstituted aromatic ring structures, Ar3 is a substituted or unsubstituted divalent aromatic ring structure, L1 is a divalent organic group or a single bond with 1 to 30 carbon atoms, X1 is a substituted or unsubstituted nitrogen atom or carbon atom, ether bond, ester bond, thioether bond, or single bond, X...) - It has the same structure as the organic sulfonyl anion molecule contained in the aforementioned (B) hot acid generating agent. Furthermore, R2, Ar1, and Ar2 can also form ring structures.

[0037] If such a composition is used for forming the resist underlayer film, the effect of the present invention can be further improved.

[0038] At this time, the aforementioned X - It should have an alicyclic structure.

[0039] If it is such a (A) polymer, its solubility can be improved and precipitation during long-term storage can be prevented by the use of a large alicyclic structure.

[0040] Furthermore, in this invention, the aforementioned polymeric compound (A) preferably does not contain structural units that satisfy the following conditions:

[0041] In a structure other than the acrylate group and methacrylate group which function as polymerizable groups, there are a total of two or more nitrogen atoms, oxygen atoms or sulfur atoms with unpaired electrons, and there are two or fewer atoms between the aforementioned two nitrogen atoms, oxygen atoms or sulfur atoms.

[0042] If such a composition is used for forming the lower layer film of a resist, it has good adhesion to various resists and can remove the residue at the bottom of the resist without increasing the pattern roughness.

[0043] Furthermore, in this invention, the ratio of the structural units containing the organic sulfonyl anion structure and the onium cation structure from the sulfur atom in the aforementioned (A) polymer compound is preferably 1 mol% or more and 30 mol% or less.

[0044] If such a composition is used for forming the lower film of the resist, it can prevent the leaching of components from polymeric compounds and hot acid generating agents during long-term storage, thus achieving good storage stability.

[0045] Furthermore, in this invention, the aforementioned (A) polymeric compound preferably has at least one structural unit represented by the following general formula (3).

[0046] [Chemistry 2]

[0047] (3)

[0048] (In the formula, R3 is a hydrogen atom or a methyl group, and R4 is a group selected from formulas (3-1) to (3-3) below.)

[0049] [Chemistry 3]

[0050]

[0051] (3-1) (3-2) (3-3)

[0052] (In the formula, dashed lines represent atomic bonds.)

[0053] By incorporating these structural units, the resist underlayer film forming composition of the present invention can achieve good curing properties without compromising adhesion to other resists.

[0054] Furthermore, in this invention, the weight-average molecular weight of the aforementioned (A) polymer compound is preferably 1,000 to 50,000.

[0055] Furthermore, in this invention, the aforementioned (C) organic solvent is preferably a mixture of one or more organic solvents with a boiling point of less than 150°C and one or more organic solvents with a boiling point of 150°C or higher and a boiling point of less than 220°C.

[0056] Furthermore, in this invention, the aforementioned composition for forming the lower layer film of the resist preferably also contains at least one selected from (D) a surfactant and (E) a crosslinking agent.

[0057] If such a composition is used for forming the lower layer of the resist film, good coatability can be obtained, and properties such as coatability and film curing properties can be finely adjusted, making it superior in practical applications.

[0058] Furthermore, this invention provides a pattern forming method, which is a method for forming a pattern on a substrate to be processed, and includes the following steps:

[0059] (I-1) After coating the resist underlayer film composition described above onto the substrate to be processed, a resist underlayer film is formed by heat treatment.

[0060] (I-2) On the aforementioned lower resist film, a photoresist material is used to form an upper resist film;

[0061] (I-3) After pattern exposure of the aforementioned upper resist film, development is performed to form a pattern on the aforementioned upper resist film;

[0062] (I-4) Using the aforementioned patterned upper resist film as a mask, the pattern is transferred to the aforementioned lower resist film by dry etching; and

[0063] (I-5) Using the aforementioned resist film with the transferred pattern as a mask, the aforementioned substrate is processed to form a pattern on the aforementioned substrate.

[0064] Furthermore, this invention provides a pattern forming method, which is a method for forming a pattern on a substrate to be processed, and includes the following steps:

[0065] (II-1) An organic film is formed on the substrate being processed;

[0066] (II-2) A silicon-containing photoresist intermediate film is formed on the aforementioned organic film;

[0067] (II-3) After coating the aforementioned silicon-containing photoresist intermediate film with the above-described composition for forming a photoresist lower layer film, a photoresist lower layer film is formed by heat treatment.

[0068] (II-4) A photoresist material is used to form an upper resist film on the aforementioned lower resist film;

[0069] (II-5) After pattern exposure of the aforementioned upper resist film, development is performed to form a pattern on the aforementioned upper resist film;

[0070] (II-6) Using the patterned upper resist film as a mask, the pattern is transferred to the lower resist film by dry etching;

[0071] (II-7) Using the aforementioned patterned lower resist film as a mask, the pattern is transferred to the aforementioned silicon-containing intermediate resist film by dry etching.

[0072] (II-8) Using the aforementioned patterned silicon-containing resist interlayer as a mask, the pattern is transferred to the aforementioned organic film by dry etching; and

[0073] (II-9) Using the aforementioned organic film with the transferred pattern as a mask, the aforementioned substrate is processed to form a pattern on the aforementioned substrate.

[0074] Furthermore, this invention provides a pattern forming method, which is a method for forming a pattern on a substrate to be processed, and includes the following steps:

[0075] (III-1) An organic film is formed on the substrate being processed;

[0076] (III-2) An inorganic hard mask intermediate film selected from silicon oxide film, silicon nitride film and silicon oxide nitride film is formed on the aforementioned organic film;

[0077] (III-3) After coating the aforementioned composition for forming a photoresist underlayer film onto the aforementioned inorganic hard mask intermediate film, a photoresist underlayer film is formed by heat treatment.

[0078] (III-4) A photoresist material is used to form an upper resist film on the aforementioned lower resist film;

[0079] (III-5) After pattern exposure of the aforementioned upper resist film, development is performed to form a pattern on the aforementioned upper resist film;

[0080] (III-6) Using the patterned upper resist film as a mask, the pattern is transferred to the lower resist film by dry etching.

[0081] (III-7) Using the aforementioned patterned resist lower layer film as a mask, the pattern is transferred to the aforementioned inorganic hard mask intermediate film by dry etching.

[0082] (III-8) Using the aforementioned inorganic hard mask intermediate film with the transferred pattern as a mask, the pattern is transferred to the aforementioned organic film by dry etching; and

[0083] (III-9) Using the aforementioned organic film with the transferred pattern as a mask, the aforementioned substrate is processed to form a pattern on the aforementioned substrate.

[0084] In this way, the composition for forming the lower resist film of the present invention can be ideally used in various pattern forming methods such as two-layer resist processes, four-layer resist processes that form the aforementioned lower resist film on a silicon-containing intermediate film (silicon-containing resist intermediate film, inorganic hard mask intermediate film), and if these pattern forming methods are used, they are suitable for optical lithography of the upper resist film.

[0085] At this point, it is advisable to use CVD or ALD to form the aforementioned inorganic hard mask intermediate film.

[0086] Furthermore, in this invention, the method for forming a pattern on the aforementioned resist film is preferably optical lithography, direct electron beam drawing, nanoimprinting, or a combination thereof with a wavelength of 10 nm or more and 300 nm or less.

[0087] Furthermore, in this invention, it is preferred to use a photoresist material comprising at least an organometallic compound and a solvent to form the aforementioned photoresist upper film.

[0088] Furthermore, in this invention, the developing method preferably uses alkaline developing, developing with organic solvents, or developing using dry etching.

[0089] In this invention, pattern formation can be performed well and efficiently by using the pattern forming method described above.

[0090] Furthermore, in this invention, the aforementioned processed substrate is preferably a semiconductor device substrate, or formed on the semiconductor device substrate using any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film.

[0091] At this time, it is preferable to use silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or alloys thereof.

[0092] If this is the pattern forming method of the present invention, then the substrate to be processed as described above can be processed in the manner described above to form a pattern.

[0093] Furthermore, this invention provides a method for forming a photoresist underlayer film, which is used in the manufacturing process of a semiconductor device. The method involves spin-coating the aforementioned photoresist underlayer film forming composition onto a substrate to be processed, and heat-treating the substrate coated with the aforementioned photoresist underlayer film forming composition at a temperature of 100°C or higher and 300°C or lower for 10 to 600 seconds to form the photoresist underlayer film.

[0094] Furthermore, the present invention provides a method for forming a photoresist underlayer film, which is used in the manufacturing process of a semiconductor device, wherein the above-described composition for forming a photoresist underlayer film is spin-coated onto a substrate to be processed, and the substrate coated with the aforementioned composition for forming a photoresist underlayer film is heat-treated in an environment with an oxygen concentration of 0.1% or more and 21% or less, thereby forming a photoresist underlayer film.

[0095] This method promotes the cross-linking reaction during the formation of the resist underlayer film, and more effectively suppresses mixing with the resist overlayer film. Furthermore, by appropriately adjusting the heat treatment temperature, time, and oxygen concentration within the aforementioned range, a pattern collapse suppression effect suitable for the application of the resist underlayer film can be achieved, and pattern shape adjustment characteristics of the resist overlayer film can be obtained.

[0096] Furthermore, this invention provides a method for forming a photoresist underlayer film, which is used in the manufacturing process of a semiconductor device. The method involves spin-coating the aforementioned composition for forming a photoresist underlayer film onto a substrate to be processed, and heat-treating the substrate coated with the aforementioned composition for forming a photoresist underlayer film in an environment with an oxygen concentration of 0.0001% or higher and less than 0.1%, thereby forming a photoresist underlayer film.

[0097] This method is useful because it prevents the degradation of the substrate even when the substrate is heated in an oxygen-containing environment. It can promote the cross-linking reaction during the formation of the lower resist film and more effectively suppress the mixing with the upper film.

[0098] [The effects of the invention]

[0099] As explained above, the present invention provides a composition for forming a resist underlayer film that prevents precipitation during long-term storage and exhibits good storage stability. This composition for forming a resist underlayer film maintains the adhesion of the resist pattern while removing residues from the bottom of the resist, making it extremely useful in steps requiring the formation of very fine patterns. Furthermore, the method for forming the resist underlayer film according to the present invention allows for sufficient curing on the processed substrate and also prevents residues from mixed resists. In particular, it is useful in the micro-patterning process performed by the multilayer resist method in semiconductor device manufacturing steps. Attached Figure Description

[0100] Figure 1 Figures (A) to (G) are illustrative diagrams of an example of the patterning method performed in the four-layer resist process of the present invention. Detailed Implementation

[0101] In this specification, when an element is described as being "directly below" another element, it is in direct contact with that element without any intervening elements. Conversely, when an element is described as being "below" another element, intervening elements can exist between them. Similarly, when an element is described as being "directly above" another element, it is in direct contact with that element without any intervening elements, and when an element is described as being "above" another element, intervening elements can exist between them.

[0102] As mentioned above, in the micro-patterning process of the multilayer resist method in the semiconductor device manufacturing process, a composition for forming a resist underlayer film is required that has good storage stability and can maintain the adhesion of the resist pattern while removing residues at the bottom of the resist.

[0103] Through repeated and in-depth investigations into the aforementioned issues, the inventors discovered that the above-mentioned issues can be resolved by using a composition for forming a photoresist underlayer film that includes a polymeric compound with a specific structure and a thermal acid generator, a method for forming a pattern of the aforementioned composition for forming a photoresist underlayer film, and a method for forming a photoresist underlayer film using the aforementioned composition for forming a photoresist underlayer film, thereby completing the present invention.

[0104] That is, the present invention is a composition for forming a resist underlayer film, comprising:

[0105] (A) A polymeric compound comprising structural units containing an organic sulfonyl anionic structure and an onium cationic structure from a sulfur atom, wherein the aforementioned onium cationic structure is dangling bonded to the polymer backbone;

[0106] (B) Thermal acid generating agent; and

[0107] (C) Organic solvents,

[0108] Furthermore, the aforementioned (A) polymeric compound and the aforementioned (B) thermal acid generating agent have the same organic sulfonyl anionic molecule.

[0109] The present invention will now be described in detail, but the present invention is not limited thereto.

[0110] [Composition for forming the lower layer film of the resist]

[0111] This invention provides a composition for forming a lower layer film of a photoresist, comprising: (A) a polymer compound containing structural units having an organic sulfonyl anionic structure and an onium cation structure from a sulfur atom, wherein the onium cation structure is dangling-bonded to the polymer backbone; (B) a thermal acid generator; and (C) an organic solvent, wherein the aforementioned polymer compound (A) and the aforementioned thermal acid generator (B) have the same organic sulfonyl anionic molecule.

[0112] Furthermore, in the composition for forming the lower layer film of the resist according to the present invention, the aforementioned polymeric compound (A) may be used alone or in combination of two or more. However, all of the aforementioned polymeric compounds (A) have the same anionic molecules as the aforementioned thermal acid generating agent (B).

[0113] [(A) Polymer compound]

[0114] The composition for forming the lower layer film of the resist of the present invention comprises (A) a polymeric compound. The structural unit comprising the aforementioned organic sulfonyl anionic structure and the onium cation structure from the sulfur atom contained in the aforementioned polymeric compound (A) is preferably represented by the following general formula (1) or (2).

[0115] [Chemistry 4]

[0116]

[0117] (In the formula, R1 is a hydrogen atom or a methyl group, R2 is a substituted or unsubstituted divalent organic group or a single bond that may also contain ether or ester bonds, Ar1 and Ar2 are substituted or unsubstituted aromatic ring structures, Ar3 is a substituted or unsubstituted divalent aromatic ring structure, L1 is a divalent organic group or a single bond with 1 to 30 carbon atoms, X1 is a substituted or unsubstituted nitrogen atom or carbon atom, ether bond, ester bond, thioether bond, or single bond, X...) - It has the same structure as the organic sulfonyl anion molecule contained in the aforementioned (B) hot acid generating agent. Furthermore, R2, Ar1, and Ar2 can also form ring structures.

[0118] In the above general formulas (1) and (2), R1 is a hydrogen atom or a methyl group.

[0119] In the above general formulas (1) and (2), R2 may be a substituted or unsubstituted divalent organic group or a single bond that may contain ether or ester bonds.

[0120] In the above general formulas (1) and (2), Ar1 and Ar2 are substituted or unsubstituted aromatic ring structures.

[0121] In the above general formula (2), Ar3 is a substituted or unsubstituted divalent aromatic ring structure.

[0122] In the above general formulas (1) and (2), L1 is a divalent organic group or a single bond with 1 to 30 carbon atoms.

[0123] In the above general formulas (1) and (2), X1 is a substituted or unsubstituted nitrogen atom or carbon atom, ether bond, ester bond, thioether bond, or single bond.

[0124] In the above general formulas (1) and (2), X - It has the same structure as the organic sulfonyl anion molecule contained in the aforementioned (B) hot acid generating agent. X - It is preferable to use an organic sulfonyl anion with 9 or more carbon atoms. Furthermore, R2, Ar1, and Ar2 can also form ring structures.

[0125] A specific example of the structure represented by the above general formula (1) can be preferably illustrated by the following structures. R1, Ar1, Ar2, X - Same as above.

[0126] [Chemistry 5]

[0127]

[0128] A specific example of the structure represented by the above general formula (2) can be preferably illustrated by the following structures. R1, Ar1, Ar2, X - Same as above.

[0129] [Chemistry 6]

[0130]

[0131] In the above general formula, the structures of Ar1 and Ar2 can be preferably illustrated as follows. However, * indicates a bond node with other structures.

[0132] [Chemistry 7]

[0133]

[0134] In the above general formulas (1) and (2), X - It is preferably any of the following general formulas (h1-1) to (h1-3), or a halogen-containing organic sulfonyl anion as described later.

[0135] [Chemistry 8]

[0136]

[0137] In the above general formulas (h1-1)~(h1-2), R 51 and R 52 Each can be independently a hydrocarbon group with 1 to 40 carbon atoms, which may also contain heteroatoms. R HF It is a hydrogen atom or a trifluoromethyl group. In the above general formula (h1-3), R 53It is a hydrocarbon group with 1 to 40 carbon atoms, consisting of a hydroxyl group, a halogen atom, or possibly a heteroatom. h4 is an integer from 0 to 5.

[0138] The anions represented by the above general formula (h1-1) may include those described in paragraphs

[0100] to

[0101] of Japanese Patent Application Publication No. 2014-177407, and those represented by the following formulas, but are not limited to these. Furthermore, in the following formulas, R... HF Same as above.

[0139] [Chemistry 9]

[0140]

[0141] [Chemistry 10]

[0142]

[0143] [Chemistry 11]

[0144]

[0145] The anions represented by the above general formula (h1-2) may include those described in paragraphs

[0080] to

[0081] of Japanese Patent Application Publication No. 2010-215608, and those represented by the following formulas, but are not limited to these. In addition, in the following formulas, Ac is an acetyl group.

[0146] [Chemistry 12]

[0147]

[0148] [Chemistry 13]

[0149]

[0150] The anions represented by the above general formula (h1-3) may be represented by the following formulas, but are not limited to these. Additionally, in the following formulas, Me represents a methyl group.

[0151] [Chemistry 14]

[0152]

[0153] [Chemistry 15]

[0154]

[0155] [Chemistry 16]

[0156]

[0157] [Chemistry 17]

[0158]

[0159] [Chemistry 18]

[0160]

[0161] In this invention, X - In addition to anions represented by the general formulas (h1-1) to (h1-3) described above, halogen-containing organic sulfonyl anions as described below are also preferred. However, in the following formulas, X BI It consists of bromine or iodine atoms.

[0162] [Chemistry 19]

[0163]

[0164] [Chemistry 20]

[0165]

[0166] [Chemistry 21]

[0167]

[0168] [Chemistry 22]

[0169]

[0170] [Chemistry 23]

[0171]

[0172] [Chemistry 24]

[0173]

[0174] [Chemistry 25]

[0175]

[0176] [Chemistry 26]

[0177]

[0178] [Chemistry 27]

[0179]

[0180] [Chemistry 28]

[0181]

[0182] [Chemistry 29]

[0183]

[0184] [Chemistry 30]

[0185]

[0186] [Chemistry 31]

[0187]

[0188] [Chemistry 32]

[0189]

[0190] [Chemistry 33]

[0191]

[0192] [Chemistry 34]

[0193]

[0194] [Chemistry 35]

[0195]

[0196] [Chemistry 36]

[0197]

[0198] [Chemistry 37]

[0199]

[0200] [Chemistry 38]

[0201]

[0202] [Chemistry 39]

[0203]

[0204] [Chemistry 40]

[0205]

[0206] [Chemistry 41]

[0207]

[0208] In this invention, the above-mentioned X - The structure used is the same as that of the organic sulfonyl anion molecule contained in (B) hot acid generating agent. This prevents ion exchange, such as the formation of new ion pairs, from occurring in the formulated composition, thus helping to prevent precipitation during long-term storage. Furthermore, the aforementioned structure supplies acid to the exposure section, improving the adhesion of the resist when using a negative resist composition, and aiding in the removal of residue from the bottom of the resist when using a positive resist composition. Also, X -By selecting those with a larger number of carbon atoms, such as 9 or more, the diffusion of this acid can be more effectively suppressed, and the increase in pattern roughness can be further suppressed.

[0209] Furthermore, the aforementioned polymeric compound (A) should preferably not contain structural units that satisfy the following conditions:

[0210] In a structure other than the acrylate group and methacrylate group which function as polymerizable groups, there are a total of two or more nitrogen atoms, oxygen atoms or sulfur atoms with unpaired electrons, and there are two or fewer atoms between the aforementioned two nitrogen atoms, oxygen atoms or sulfur atoms.

[0211] Structural units that meet the foregoing conditions preferably do not contain structural units that contain partial structures represented by the following general formulas (P1) or (P2).

[0212] [Chemistry 42]

[0213]

[0214] (where X) 1 and X 2 Each can be independently an oxygen atom, a sulfur atom, or a nitrogen atom. The spaces between C and C in the above general formula (P1), and X in the above general formula (P2) 1 Between and to the left of C, and X 2 The following formulas between C and the right side represent single or double bonds, respectively.

[0215] [Chemistry 43]

[0216]

[0217] As a part of the above general formula (P1) or (P2), the following examples can be given.

[0218] [Chemistry 44]

[0219]

[0220] When structural units that meet the conditions described above are included, these structures may interact strongly with the resist composition, potentially leading to residue buildup at the bottom of the resist. To prevent this, it is preferable to exclude these structural units.

[0221] In the aforementioned general formula (1) or (2), the aforementioned X - It should preferably have an alicyclic structure, and more preferably not contain an aromatic ring.

[0222] The relatively large alicyclic structure improves solubility and prevents precipitation during long-term storage. Furthermore, the large structure shortens the diffusion length of anions, preventing an increase in pattern roughness. When aromatic rings are present, the solubility is slightly worse due to intermolecular interactions caused by packing; therefore, those without aromatic rings are preferred.

[0223] In the aforementioned (A) polymer compound, the ratio of the aforementioned structural units containing an organic sulfonyl anionic structure and an onium cation structure from a sulfur atom is preferably 1 mol% to 30 mol% or more, and more preferably 1 mol% to 20 mol% or less.

[0224] The above structural units have salt structures, and considering the solubility of polymers, a low content is preferable.

[0225] The aforementioned (A) polymeric compound preferably has at least one structural unit represented by the following general formula (3), and preferably includes two or more.

[0226] [Chemistry 45]

[0227] (3)

[0228] (In the formula, R3 is a hydrogen atom or a methyl group, and R4 is a group selected from formulas (3-1) to (3-3) below.)

[0229] [Chemistry 46]

[0230]

[0231] (3-1) (3-2) (3-3)

[0232] (In the formula, dashed lines represent atomic bonds.)

[0233] The aforementioned structural units function as crosslinking groups and form hydroxyl and ether structures after crosslinking, thus improving adhesion. Using a variety of these structural units and adjusting their composition ratio allows for control of film properties such as curability and contact angle according to usage conditions, making it superior in practical applications.

[0234] Furthermore, in this invention, the weight-average molecular weight of the aforementioned (A) polymer compound is preferably 1,000 to 50,000, and more preferably 20,000 to 40,000. Additionally, this weight-average molecular weight is a value converted from polystyrene or polymethyl methacrylate determined using gel permeation chromatography (GPC) with a fluorinated solvent such as tetrahydrofuran (THF), N,N-dimethylformamide (DMF), or 1,1,1,3,3,3-hexafluoro-2-propanol as the eluent.

[0235] If the molecular weight band is such, it can prevent poor coating caused by the sublimation of low molecular weight components and defects caused by high molecular weight components, and can obtain good coating properties and defect performance.

[0236] [(B) Thermal acid generating agent]

[0237] The hot acid generator (B) contained in the composition for forming the lower layer film of the resist of the present invention is not particularly limited as long as it has the same organic sulfonyl anion molecule as the aforementioned (A) polymer compound, and is preferably a structure represented by the following general formula (4).

[0238] [Chemistry 47]

[0239] (4)

[0240] (where X) - To have the same structure as the organic sulfonyl anion molecule contained in the aforementioned polymer compound (A). R8, R9, R 10 and R 11 These groups represent hydrogen atoms, or linear, branched, or cyclic alkyl, alkenyl, oxoalkyl, or oxoalkenyl groups having 1 to 12 carbon atoms, aryl groups having 6 to 20 carbon atoms, or aralkyl or aryloxoalkyl groups having 7 to 12 carbon atoms. Some or all of the hydrogen atoms in these groups may be substituted with alkoxy groups, etc. Also, R8 and R9, R8 and R9 and R... 10 It can also form a loop, and when a loop is formed, R8 and R9, and R8 and R9 and R... 10 (This refers to an alkylene group having 3 to 10 carbon atoms, or a heteroaromatic ring having a nitrogen atom in the formula.)

[0241] In the above general formula (4), R8, R9, R 10 and R 11Alkyl groups can be the same as or different from each other. Specifically, examples of alkyl groups include: methyl, ethyl, propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclopropylmethyl, 4-methylcyclohexyl, cyclohexylmethyl, norbornel, adamantyl, etc. Examples of alkenyl groups include: vinyl, allyl, propenyl, butenyl, hexenyl, cyclohexenyl, etc. Examples of oxoalkyl groups include: 2-oxocyclopentyl, 2-oxocyclohexyl, 2-oxopropyl, 2-cyclopentyl-2-oxoethyl, 2-cyclohexyl-2-oxoethyl, 2-(4-methylcyclohexyl)-2-oxoethyl, etc. Examples of oxoalkenyl groups include: 2-oxo-4-cyclohexenyl, 2-oxo-4-propenyl, etc. Aryl groups can be listed as: phenyl, naphthyl, etc.; p-methoxyphenyl, m-methoxyphenyl, o-methoxyphenyl, ethoxyphenyl, p-tert-butoxyphenyl, m-tert-butoxyphenyl, etc. (alkoxyphenyl groups); 2-tolyl, 3-tolyl, 4-tolyl, ethylphenyl, 4-tert-butphenyl, 4-butphenyl, xylylyl, etc. (alkylphenyl groups); methylnaphthyl, ethylnaphthyl, etc. (alkylnaphthyl groups); methoxynaphthyl, ethoxynaphthyl, etc. (alkoxynaphthyl groups); dimethylnaphthyl, diethylnaphthyl, etc. (dialkylnaphthyl groups); dimethoxynaphthyl, diethoxynaphthyl, etc. (dialkoxynaphthyl groups); etc. Arylalkyl groups can be listed as: benzyl, phenylethyl, phenethyl, etc. Aryloxoalkyl groups can be listed as: 2-phenyl-2-oxoethyl, 2-(1-naphthyl)-2-oxoethyl, 2-(2-naphthyl)-2-oxoethyl, etc. (2-aryl-2-oxoethyl groups); etc.

[0242] Also, R8, R9, R 10 R 11Examples of heteroaromatic rings containing nitrogen atoms in the formula include: imidazole derivatives (e.g., imidazole, 4-methylimidazolium, 4-methyl-2-phenylimidazolium, etc.), pyrazole derivatives, furazan derivatives, pyrroline derivatives (e.g., pyrroline, 2-methyl-1-pyrroline, etc.), pyrrolidine derivatives (e.g., pyrrolidine, N-methylpyrrolidine, pyrrolidone, N-methylpyrrolidone, etc.), imidazoline derivatives, imidazodinium derivatives, pyridine derivatives (e.g., pyridine, methylpyridine, ethylpyridine, propylpyridine, butylpyridine, 4-(1-butylpentyl)pyridine, dimethylpyridine, trimethylpyridine, triethylpyridine, phenylpyridine, 3-methyl-2-phenylpyridine, 4-tert-butylpyridine, diphenylpyridine, benzylpyridine, methoxypyridine, butoxypyridine, dimethoxypyridine, 1-methyl-2-pyridine). Ketones, 4-pyrrolylpyridine, 1-methyl-4-phenylpyridine, 2-(1-ethylpropyl)pyridine, aminopyridine, dimethylaminopyridine, etc.), pyridazine derivatives, pyrimidine derivatives, pyrazine derivatives, pyrazoline derivatives, pyrazolidine derivatives, piperidine derivatives, piperazine derivatives, morpholine derivatives, indole derivatives, isoindole derivatives, 1H-indazole derivatives, indoleline derivatives, quinoline derivatives (e.g., quinoline, 3-quinoline nitrile, etc.), isoquinoline derivatives, cyclophosphine derivatives, quinazoline derivatives, quinoxaline derivatives, phthalazine derivatives, purine derivatives, pteridine derivatives, carbazole derivatives, phenanthridine derivatives, acridine derivatives, phenazine derivatives, 1,10-phenanthroline derivatives, adenine derivatives, adenosine derivatives, guanine derivatives, guanosine derivatives, uracil derivatives, ureosine derivatives, etc.

[0243] In this invention, the above-mentioned X - It has the same structure as the organic sulfonyl anion molecule contained in the aforementioned polymer (A). A specific structure can be exemplified by X in the above general formulas (1) and (2). - The same examples.

[0244] In this invention, one or more types of hot acid generating agents (B) may be used, but when two or more types are used, all of the hot acid generating agents should preferably have the same structure as the organic sulfonyl anion molecule contained in the aforementioned polymer compound (A). By selecting such a hot acid generating agent, the precipitation of components from the resin and the hot acid generating agent can be prevented during long-term storage, resulting in excellent storage stability. It is also expected to suppress defects caused by precipitates generated during film formation, and not only can the storage stability of the composition used to form the resist underlayer film be expected, but also an improvement in quality can be anticipated.

[0245] (B) The amount of the hot acid generating agent added relative to 100 parts by mass of (A) polymer compound should preferably be 0.1 to 10 parts by mass, and more preferably 0.1 to 3 parts by mass.

[0246] [(C) Organic solvent]

[0247] The organic solvent (C) in the composition for forming the lower layer film of the resist of the present invention is not particularly limited as long as it is a solvent that dissolves the aforementioned (A) polymer compound and (B) hot acid generator, and other additives, if present. However, it is preferably a mixture of one or more organic solvents with a boiling point of less than 150°C and one or more organic solvents with a boiling point of 150°C or higher and a boiling point of less than 220°C. Specifically, the following can be used: ketones such as cyclohexanone, cyclopentanone, methyl-2-n-pentyl ketone, and 2-heptanone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, and diacetone alcohol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, propylene glycol monotert-butyl ether acetate, and lactones such as γ-butyrolactone. For organic solvents with a boiling point below 150°C, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, cyclopentanone, and mixtures thereof are preferred. For organic solvents with a boiling point above 150°C but below 220°C, cyclohexanone, diacetone alcohol, ethyl lactate, γ-butyrolactone, and mixtures thereof are preferred.

[0248] (C) The amount of organic solvent added should be 5,000 to 100,000 parts by mass relative to 100 parts by mass of (A) polymer compound.

[0249] [additive]

[0250] The resist underlayer film forming composition of the present invention, in addition to the components (A) to (C) described above, may also contain at least one selected from (D) surfactant and (E) crosslinking agent. By adjusting the type and amount of these materials, various properties of the composition, such as curing temperature, coatability, and patterning performance, can be optimized. Each component is described below.

[0251] [(D) Surfactant]

[0252] In the composition for forming the lower layer film of the resist of the present invention, a surfactant (D) may be added to improve the coatability during spin coating. The surfactant (D) may be used alone or in combination of two or more. The surfactant (D) may be, for example, those described in

[0142] to

[0147] of Japanese Patent Application Publication No. 2009-269953. The amount of surfactant (D) added is preferably 0.001 to 20 parts by weight, more preferably 0.01 to 10 parts by weight, relative to 100 parts by weight of the aforementioned polymeric compound (A).

[0253] [(E) Crosslinking agent]

[0254] Furthermore, in the composition for forming the lower layer film of the resist according to the present invention, a crosslinking agent (E) may be added to improve curability and further suppress miscibility with the upper layer film of the resist. The crosslinking agent is not particularly limited, and various known crosslinking agents can be widely used. Examples include: melamine-based crosslinking agents, acetylene urea-based crosslinking agents, benzoguanamine-based crosslinking agents, urea-based crosslinking agents, β-hydroxyalkylamide-based crosslinking agents, isocyanurate-based crosslinking agents, aziridine-based crosslinking agents, oxazoline-based crosslinking agents, epoxy-based crosslinking agents, and phenol-based crosslinking agents. One type of crosslinking agent (E) may be used alone or in combination of two or more. The amount of crosslinking agent (E) added relative to 100 parts by weight of the aforementioned polymer compound (A) is preferably 5 to 50 parts by weight, and more preferably 10 to 40 parts by weight. If the amount added is 5 parts by weight or more, sufficient curability is exhibited, and miscibility with the upper layer film of the resist can be suppressed. On the other hand, if the amount added is less than 50 parts by mass, there is a risk of deterioration in the adhesion due to a decrease in the proportion of (A) polymeric compounds in the composition.

[0255] Melamine-based crosslinking agents can be specifically exemplified as: hexamethoxymethylated melamine, hexabutoxymethylated melamine, their alkoxy and / or hydroxyl substituents, and their partial self-condensation compounds.

[0256] Specifically, examples of acetylurea crosslinking agents include: tetramethoxymethylated acetylurea, tetrabutoxymethylated acetylurea, their alkoxy and / or hydroxyl substituents, and their partial self-condensation compounds.

[0257] Benzylguanidine crosslinking agents can be specifically exemplified as: tetramethoxymethylated benzoguanidine, tetrabutoxymethylated benzoguanidine, their alkoxy and / or hydroxy substituted forms, and their partial self-condensation compounds.

[0258] Urea-based crosslinking agents can be specifically exemplified as: dimethoxymethylated dimethoxyethylene urea, its alkoxy and / or hydroxy substituted forms, and their partial self-condensation compounds.

[0259] β-hydroxyalkylamide crosslinking agents can be specifically exemplified by N,N,N',N'-tetra(2-hydroxyethyl) adipamide.

[0260] Isocyanurate crosslinking agents can be specifically exemplified by tricyclooxypropyl isocyanurate and triallyl isocyanurate.

[0261] Aziridine-based crosslinking agents can be specifically exemplified by: 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane, 2,2-dihydroxymethylbutanol-tris[3-(1-aziridine)propionate].

[0262] Oxazoline-based crosslinking agents can be specifically exemplified as: 2,2'-isopropylidene bis(4-benzyl-2-oxazoline), 2,2'-isopropylidene bis(4-phenyl-2-oxazoline), 2,2'-methylene bis(4,5-diphenyl-2-oxazoline), 2,2'-methylene bis(4-phenyl-2-oxazoline), 2,2'-methylene bis(4-tert-butyl-2-oxazoline), 2,2'-bis(2-oxazoline), 1,3-phenylene bis(2-oxazoline), 1,4-phenylene bis(2-oxazoline), and 2-isopropylidene oxazoline copolymers.

[0263] Epoxy crosslinking agents can be specifically exemplified as: diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanediethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and neopentyl tertetrol tetraglycidyl ether.

[0264] Specifically, examples of polyphenol-based crosslinking agents include compounds represented by the following general formula (6).

[0265] [Chemistry 48]

[0266] (6)

[0267] (In the formula, Q is a single bond, or a q-valent hydrocarbon group with 1 to 20 carbon atoms. R) 14 It consists of hydrogen atoms or alkyl groups having 1 to 20 carbon atoms. q is an integer from 1 to 5.

[0268] In the above general formula (6), Q is a single bond or a q-valent hydrocarbon group with 1 to 20 carbon atoms. q is an integer from 1 to 5, preferably 2 or 3. Specifically, Q can be exemplified by: methane, ethane, propane, butane, isobutane, pentane, cyclopentane, hexane, cyclohexane, methylpentane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, benzene, toluene, xylene, ethylbenzene, ethylisopropylbenzene, diisopropylbenzene, methylnaphthalene, ethylnaphthalene, and those formed by removing q hydrogen atoms from eicosane. R 14It is a hydrogen atom or an alkyl group having 1 to 20 carbon atoms. Specifically, examples of alkyl groups having 1 to 20 carbon atoms include: methyl, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, isopentyl, hexyl, octyl, ethylhexyl, decyl, and eicosyl, preferably with a hydrogen atom or a methyl atom.

[0269] Specifically, examples of compounds represented by the above general formula (6) can be illustrated by the following compounds. Among them, considering the viewpoint of improving the curability and film thickness uniformity of the underlayer film of the resist, triphenol methane, triphenol ethane, 1,1,1-tris(4-hydroxyphenyl)ethane, and hexamethoxymethylated derivatives of tris(4-hydroxyphenyl)-1-ethyl-4-isopropylbenzene are preferred.

[0270] [Chemistry 49]

[0271]

[0272] [Transformation 50]

[0273]

[0274] (E) The crosslinking agent can be used alone or in combination of two or more. The amount of crosslinking agent (E) added relative to 100 parts by mass of the aforementioned polymer (A) is preferably 5% to 50% by mass, and more preferably 10% to 40% by mass. If the amount added is 5% by mass or more, sufficient curing properties are achieved, and intermixing with the upper layer of the resist film can be suppressed. On the other hand, if the amount added is 50% by mass or less, the proportion of polymer (A) in the composition will not become too low, and the benefits of improved photolithography properties of the resist due to the organic sulfonyl anionic structure, etc., in polymer (A) can be fully enjoyed.

[0275] The thickness of the resist lower layer film obtained from the composition for forming the resist lower layer film of the present invention can be appropriately selected, but it is preferable to adjust it to 2~100nm, and it is especially preferred to adjust it to 5~20nm.

[0276] Furthermore, the composition for forming the resist underlayer film of the present invention is extremely useful as a resist underlayer film material for multilayer resist processes such as two-layer resist processes and four-layer resist processes using organic films and silicon-containing intermediate films.

[0277] The aforementioned silicon-containing interlayer film can be used as a silicon-containing photoresist interlayer film or an inorganic hard mask interlayer film, depending on the patterning method described later. The aforementioned inorganic hard mask interlayer film is preferably selected from silicon oxide films, silicon nitride films, and silicon oxide nitride films.

[0278] [Methods for forming the underlayer of the resist]

[0279] In this invention, using the aforementioned composition for forming a photoresist underlayer, a method for forming a photoresist underlayer is provided. This method maintains good photoresist adhesion and improves residue removal at the bottom of the photoresist layer during the micro-patterning process of the multilayer photoresist method in semiconductor device manufacturing. Specifically, this invention provides a method for forming a photoresist underlayer, used in the manufacturing process of a semiconductor device. The method involves spin-coating the aforementioned composition for forming a photoresist underlayer onto a substrate, and then heat-treating the substrate coated with the aforementioned composition at a temperature between 100°C and 300°C for 10 to 600 seconds to form the photoresist underlayer.

[0280] In the method for forming the resist underlayer film of the present invention, the aforementioned composition for forming the resist underlayer film is coated onto a substrate to be processed by a spin coating method or the like. After spin coating, the organic solvent is evaporated, and in order to prevent mixing with the resist upper layer film and the silicon-containing intermediate film, baking (heat treatment) is performed to promote the crosslinking reaction. Baking is preferably performed in the range of 100°C to 300°C for 10 to 600 seconds, preferably in the range of 200°C to 250°C for 10 to 300 seconds. Considering the impact on damage to the resist underlayer film and deformation of the wafer, the upper limit of the heating temperature in the photolithography wafer fabrication process is preferably set to 300°C or lower, preferably 250°C or lower.

[0281] Furthermore, in the method for forming the resist underlayer film of the present invention, the resist underlayer film forming composition of the present invention may be coated onto a substrate by the same spin coating method as described above, and the resist underlayer film forming composition may be calcined in an environment with an oxygen concentration of 0.1% or more and 21% or less to solidify it, thereby forming the resist underlayer film. That is, the present invention provides a method for forming a resist underlayer film used in the manufacturing process of a semiconductor device, wherein the resist underlayer film forming composition described above is spin-coated onto a substrate, and the substrate coated with the resist underlayer film forming composition is heat-treated in an environment with an oxygen concentration of 0.1% or more and 21% or less to form the resist underlayer film. By calcining the resist underlayer film forming composition of the present invention in such an oxygen environment, a sufficiently cured resist underlayer film can be obtained.

[0282] The baking environment can be not only in air, but also sealed with inert gases such as N2, Ar, and He. In this case, the environment can be adjusted to have an oxygen concentration of 0.0001% or higher but less than 0.1%. That is, this invention provides a method for forming a photoresist underlayer film, used in the manufacturing process of a semiconductor device. The method involves spin-coating the aforementioned photoresist underlayer film forming composition onto a substrate, and then heat-treating the substrate coated with the aforementioned photoresist underlayer film forming composition in an environment with an oxygen concentration of 0.0001% or higher but less than 0.1%, thereby forming the photoresist underlayer film. Furthermore, the baking temperature and other parameters can be set as described above. Even when the substrate is a material that is unstable when heated in an oxygen-containing environment, the substrate will not deteriorate, and the cross-linking reaction during the formation of the photoresist underlayer film can be promoted.

[0283] [Pattern Formation Method]

[0284] This invention provides a pattern forming method, which is a method for forming a pattern on a substrate to be processed, and includes the following steps:

[0285] (I-1) After coating the resist underlayer film composition described above on the substrate to be processed, a resist underlayer film is formed by heat treatment.

[0286] (I-2) On the aforementioned lower resist film, a photoresist material is used to form an upper resist film;

[0287] (I-3) After pattern exposure of the aforementioned upper resist film, development is performed to form a pattern on the aforementioned upper resist film;

[0288] (I-4) Using the aforementioned patterned upper resist film as a mask, the pattern is transferred to the aforementioned lower resist film by dry etching; and

[0289] (I-5) Using the aforementioned resist film with the transferred pattern as a mask, the aforementioned substrate is processed to form a pattern on the aforementioned substrate.

[0290] Regarding the pattern forming method of the present invention, a four-layer resist process will be used as an example for explanation below, but the present invention is not limited to this process. First, a pattern forming method is provided, which is a method for forming a pattern on a substrate to be processed, and includes at least the following steps: forming an organic film on the substrate to be processed using an organic film material; forming a silicon-containing intermediate film (silicon-containing resist intermediate film) on the aforementioned organic film using a resist intermediate film material containing silicon atoms; forming a resist lower layer film on the aforementioned silicon-containing resist intermediate film using a resist lower layer film forming composition of the present invention; forming a resist upper layer film (photoresist material) on the aforementioned resist lower layer film using a resist upper layer film material (photoresist material) composed of a photoresist composition and serving as a multilayer resist film; and forming a patterned circuit area on the aforementioned resist upper layer film. After exposure in the region, development is performed to form a resist upper layer film pattern; the obtained resist upper layer film pattern is used as an etching mask to etch the resist lower layer film to form a resist lower layer film pattern; the obtained resist lower layer film pattern is used as an etching mask to etch the silicon-containing resist intermediate film to form a silicon-containing resist intermediate film pattern; the obtained silicon-containing resist intermediate film pattern is used as an etching mask to etch the organic film to form an organic film pattern; further, the obtained organic film pattern is used as an etching mask to etch the processed substrate to form a pattern on the processed substrate.

[0291] That is, the present invention provides a pattern forming method, which is a method for forming a pattern on a substrate to be processed, and includes the following steps:

[0292] (II-1) An organic film is formed on the substrate being processed;

[0293] (II-2) A silicon-containing photoresist intermediate film is formed on the aforementioned organic film;

[0294] (II-3) After coating the aforementioned silicon-containing photoresist intermediate film with the above-described composition for forming a photoresist lower layer film, a photoresist lower layer film is formed by heat treatment.

[0295] (II-4) A photoresist material is used to form an upper resist film on the aforementioned lower resist film;

[0296] (II-5) After pattern exposure of the aforementioned upper resist film, development is performed to form a pattern on the aforementioned upper resist film;

[0297] (II-6) Using the patterned upper resist film as a mask, the pattern is transferred to the lower resist film by dry etching;

[0298] (II-7) Using the aforementioned patterned lower resist film as a mask, the pattern is transferred to the aforementioned silicon-containing intermediate resist film by dry etching.

[0299] (II-8) Using the aforementioned patterned silicon-containing resist interlayer as a mask, the pattern is transferred to the aforementioned organic film by dry etching; and

[0300] (II-9) Using the aforementioned organic film with the transferred pattern as a mask, the aforementioned substrate is processed to form a pattern on the aforementioned substrate.

[0301] In the aforementioned four-layer resist process, a polysilicon silsesquioxane-based interlayer is preferred as the silicon-containing resist interlayer. By giving the silicon-containing resist interlayer an anti-reflective effect, reflection can be suppressed. Especially for 193nm exposure, if a material containing a large number of aromatic groups and with high substrate etching resistance is used as an organic film, the k-value becomes high, and the substrate reflection becomes high. However, by using a silicon-containing resist interlayer to suppress reflection, the substrate reflection can be adjusted to below 0.5%. As a silicon-containing resist interlayer with anti-reflective effect, anthracene is preferable for 248nm and 157nm exposure, while for 193nm exposure, a polysilicon silsesquioxane with phenyl or silicon-silicon bonded light-absorbing groups and cross-linked by acid or heat is preferable.

[0302] In this case, compared with the CVD method, the method of forming silicon-containing photoresist intermediate film by spin coating is simpler and more cost-effective.

[0303] Alternatively, an inorganic hard mask intermediate film can be formed as a silicon-containing intermediate film. In this case, at least the following steps are possible: forming an organic film on the substrate being processed using an organic film material; forming an inorganic hard mask intermediate film selected from silicon oxide film, silicon nitride film, and silicon oxide nitride film on the aforementioned organic film; forming a lower resist film on the aforementioned inorganic hard mask intermediate film using the resist lower layer film forming composition of the present invention; forming a resist upper layer film on the aforementioned resist lower layer film using a resist upper layer film material (photoresist material) composed of a photoresist composition and serving as a multilayer resist film; and exposing the patterned circuit area of ​​the aforementioned resist upper layer film. Subsequently, development is performed to form a resist upper layer film pattern; the obtained resist upper layer film pattern is used as an etching mask to etch the aforementioned resist lower layer film to form a resist lower layer film pattern; the obtained resist lower layer film pattern is used as an etching mask to etch the aforementioned inorganic hard mask intermediate film to form an inorganic hard mask intermediate film pattern; the obtained inorganic hard mask intermediate film pattern is used as an etching mask to etch the aforementioned organic film to form an organic film pattern; further, the obtained organic film pattern is used as an etching mask to etch the aforementioned substrate to form a pattern on the aforementioned substrate to be processed.

[0304] That is, the present invention provides a pattern forming method, which is a method for forming a pattern on a substrate to be processed, and includes the following steps:

[0305] (III-1) An organic film is formed on the substrate being processed;

[0306] (III-2) An inorganic hard mask intermediate film selected from silicon oxide film, silicon nitride film and silicon oxide nitride film is formed on the aforementioned organic film;

[0307] (III-3) After coating the aforementioned composition for forming a photoresist underlayer film onto the aforementioned inorganic hard mask intermediate film, a photoresist underlayer film is formed by heat treatment.

[0308] (III-4) A photoresist material is used to form an upper resist film on the aforementioned lower resist film;

[0309] (III-5) After pattern exposure of the aforementioned upper resist film, development is performed to form a pattern on the aforementioned upper resist film;

[0310] (III-6) Using the patterned upper resist film as a mask, the pattern is transferred to the lower resist film by dry etching.

[0311] (III-7) Using the aforementioned patterned resist lower layer film as a mask, the pattern is transferred to the aforementioned inorganic hard mask intermediate film by dry etching.

[0312] (III-8) Using the aforementioned inorganic hard mask intermediate film with the transferred pattern as a mask, the pattern is transferred to the aforementioned organic film by dry etching; and

[0313] (III-9) Using the aforementioned organic film with the transferred pattern as a mask, the aforementioned substrate is processed to form a pattern on the aforementioned substrate.

[0314] As mentioned above, when forming an inorganic hard mask interlayer on an organic film, silicon oxide films, silicon nitride films, and silicon oxide nitride films (SiON films) can be formed using methods such as CVD and ALD. That is, CVD or ALD methods are preferred for forming the aforementioned inorganic hard mask interlayer. For example, a method for forming a silicon nitride film is described in Japanese Patent Application Publication No. 2002-334869 and International Publication No. 2004 / 066377. The thickness of the inorganic hard mask interlayer is preferably 5-200 nm, more preferably 10-100 nm. Furthermore, the inorganic hard mask interlayer is preferably a SiON film with high anti-reflective properties. Since the substrate temperature during SiON film formation is 300-500°C, the organic film needs to withstand temperatures of 300-500°C.

[0315] The upper resist film in the aforementioned four-layer photoresist process can be either positive or negative, and can be the same as commonly used photoresist materials. Furthermore, it is preferable to use a photoresist material containing at least an organometallic compound and a solvent to form the aforementioned upper resist film. The organometallic compound preferably includes at least one selected from titanium, cobalt, copper, zinc, zirconium, lead, indium, tin, antimony, and hafnium, but is not limited to these. For example, solvents such as 4-methyl-2-pentanol can be used, but are not limited to these. After spin-coating the photoresist material, pre-baking is preferably performed at 60-180°C for 10-300 seconds. Subsequently, exposure is performed according to common methods, followed by post-exposure baking (PEB) and development to obtain the upper resist film pattern. In addition, the thickness of the upper resist film is not particularly limited, but is preferably 30-500 nm, and particularly 50-400 nm.

[0316] When the aforementioned photoresist top layer is formed using a photoresist material containing at least an organometallic compound and a solvent, it has the effect of suppressing the collapse of fine patterns and allows for appropriate adjustment of the pattern shape and exposure sensitivity of the photoresist top layer. Simultaneously, it prevents contamination of the processed substrate caused by organometallic compounds when using photoresist materials containing organometallic compounds and solvents.

[0317] A circuit pattern (resist over film pattern) is formed on the resist over film. The method for forming the aforementioned resist over film pattern is preferably optical lithography, direct electron beam drawing, nanoimprinting, or a combination thereof with a wavelength of 10 nm or more and 300 nm or less.

[0318] In addition, the exposed light is high-energy radiation with wavelengths below 300nm, specifically including: far ultraviolet light, KrF excimer laser (248nm), ArF excimer laser (193nm), F2 laser (157nm), Kr2 laser (146nm), Ar2 laser (126nm), soft X-rays (EUV) with wavelengths of 3~20nm, electron beam (EB), ion beam, X-rays, etc.

[0319] Furthermore, in the formation of circuit patterns, the development method should preferably be alkaline development, development using organic solvents, or dry etching development.

[0320] Next, the obtained upper resist film pattern is used as a mask for etching. In the four-layer resist process, the etching of the lower resist film obtained from the composition for forming the lower resist film of the present invention is performed using an oxygen-based gas and with the upper resist film pattern used as a mask. This forms the lower resist film pattern.

[0321] Then, the aforementioned resist underlayer pattern is used as a mask for etching. The etching of the silicon-containing resist intermediate film and the inorganic hard mask intermediate film is performed using a chlorofluorocarbon-based gas and with the aforementioned resist underlayer pattern used as a mask. This forms the silicon-containing resist intermediate film pattern and the inorganic hard mask intermediate film pattern.

[0322] Sometimes the etching of the aforementioned photoresist underlayer film can be performed continuously before the etching of the silicon-containing intermediate film, or the etching of the silicon-containing intermediate film can be performed by changing the etching apparatus after only the etching of the aforementioned photoresist underlayer film is performed.

[0323] Then, using the obtained silicon-containing photoresist intermediate film pattern and inorganic hard mask intermediate film pattern as masks, the organic film is etched. The etching of the organic film is performed using oxygen or hydrogen gas, with the aforementioned silicon-containing photoresist intermediate film pattern and inorganic hard mask intermediate film pattern used as masks. In this way, an organic film pattern is formed.

[0324] The subsequent etching of the substrate can also be performed using common methods. For example, if the substrate is a low-dielectric-constant insulating film based on SiO2, SiN, or silicon dioxide, etching with chlorofluorocarbon (CFC) gases as the primary method is performed; if it is p-Si, Al, or W, etching with chlorine or bromine gases as the primary method is performed. When etching the substrate with CFC gases, the silicon-containing interlayer pattern in the four-layer resist process is stripped simultaneously with the substrate processing. When etching the substrate with chlorine or bromine gases, the removal of the silicon-containing interlayer pattern requires separate dry etching with CFC gases after the substrate processing.

[0325] Furthermore, the aforementioned substrate being processed is not particularly limited and can be any one of a semiconductor device substrate, or a metal film, metal carbide film, metal oxide film, metal nitride film, metal oxide carbide film, and metal oxide nitride film formed on the semiconductor device substrate. The aforementioned metal can be silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or alloys thereof.

[0326] Specifically, substrates such as Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, and Al can be used, and the layer to be processed can be formed on these substrates. The layer to be processed uses various Low-k films and their barrier films, such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, and Al-Si, and can typically be formed with a thickness of 50–10,000 nm, particularly 100–5,000 nm. Furthermore, the substrate and the layer to be processed can be made of different materials when forming the layer.

[0327] For an example of a 4-layer resist process, if using Figure 1 Specifically, it is expressed as follows. The case of a 4-layer resist process is as follows: Figure 1 As shown in (A), after forming an organic film 3 on a processed layer 2 stacked on a substrate 1 using an organic film material, a silicon-containing intermediate film 4 is formed, a photoresist lower layer film 5 is formed thereon using the composition for forming a photoresist lower layer film of the present invention, and a photoresist upper layer film 6 is formed thereon.

[0328] Then, as Figure 1 As shown in (B), the desired portion 7 of the resist upper film is exposed, and PEB and development are performed to form the resist upper film pattern 6a. Figure 1 (C)). Using the obtained upper resist film pattern 6a as a mask, the lower resist film 5 is etched using O2-based gas to form the lower resist film pattern 5a. Figure 1 (D)). Using the obtained resist lower film pattern 5a as a mask, the silicon-containing intermediate film 4 is etched using CF-based gas to form the silicon-containing intermediate film pattern 4a. Figure 1 (E)). After removing the resist underlayer pattern 5a, the resulting silicon-containing intermediate pattern 4a is used as a mask to etch the organic film 3 using O2-based gas, forming the organic film pattern 3a. Figure 1 (F)). After further removing the silicon-containing intermediate film pattern 4a, the organic film pattern 3a is used as a mask to etch the layer 2 to form pattern 2a. Figure 1 (G)).

[0329] Thus, if it is the pattern forming method of the present invention, then in the multilayer resist process, fine patterns can be formed with high precision on the substrate being processed.

[0330] Example

[0331] The present invention will be described in more detail below with examples of synthesis, comparative synthesis, examples, and comparative examples, but the present invention is not limited thereto. Furthermore, the molecular weight was determined by gel permeation chromatography (GPC) using fluorinated solvents such as tetrahydrofuran (THF), N,N-dimethylformamide (DMF), or 1,1,1,3,3,3-hexafluoro-2-propanol as the eluent, and the dispersion (Mw / Mn) was determined from the weight-average molecular weight (Mw) and number-average molecular weight (Mn) converted from polystyrene or polymethyl methacrylate.

[0332] In the synthesis of polymers (A1) to (A43) and comparative polymers (R1) to (R4) used as components for forming the lower layer film of the resist, monomers (B1) to (B22) as shown below are used.

[0333] [Chemistry 51]

[0334]

[0335] [Synthesis Example 1] Synthesis of Polymer (A1)

[0336] In a nitrogen environment, 64.9 g of monomer (B1), 35.1 g of monomer (B10), 5.84 g of V-601 (dimethyl 2,2'-azobis(isobutyrate), manufactured by Wako Pure Chemical Industries, Ltd.), and 340 g of DAA (diacetone alcohol) were weighed into a 1 L flask and degassed while stirring to prepare a monomer-polymerization initiator solution. In another 1 L flask adjusted to a nitrogen environment, 60 g of DAA was weighed and degassed while stirring, then heated to 80°C. The monomer-polymerization initiator solution was added dropwise over 4 hours, and the polymerization solution was maintained at 80°C with continuous stirring for 16 hours, followed by cooling to room temperature. The resulting polymer solution was then added dropwise to 1,500 g of vigorously stirred hexane, and the precipitated polymer was separated by filtration. Furthermore, the obtained polymer was washed twice with 600g of hexane and then vacuum dried at 50°C for 20 hours to obtain a white powder polymer (A1) (yield 90.2g, 90% yield). The weight-average molecular weight (Mw) and dispersity (Mw / Mn) of polymer (A1) were determined by GPC: Mw = 23,400, Mw / Mn = 1.7.

[0337] [Chemistry 52]

[0338]

[0339] Synthesis Examples 2-43, Comparative Synthesis Examples 1-4] Synthesis of polymers (A2)-(A43), and comparative polymers (R1)-(R4)

[0340] By changing the type of monomer, the monomer blending ratio, and the amount of polymerization initiator, but otherwise under the same reaction and post-treatment conditions as in Synthesis Example 1, polymers (A2) to (A43) and comparative polymers (R1) to (R4) shown in Tables 1 and 2 were obtained as products. The weight-average molecular weight (Mw) and dispersion (Mw / Mn) obtained by GPC are also shown.

[0341] [Table 1]

[0342]

[0343] [Table 2]

[0344]

[0345] [Preparation of compositions for forming the lower layer of resist (AL-1~52, comparative AL-1~8)]

[0346] Using the polymers (A1) to (A43), comparative polymers (R1) to (R4), additives (AD1) to (AD10) as shown below, propylene glycol monomethyl ether acetate (PGMEA), diacetone alcohol (DAA), ethyl lactate (EL), and cyclohexanone (CyHO) containing 0.01% by mass of PF636 (manufactured by OMNOVA), and dissolved in the proportions shown in Tables 3 and 4, the solutions were filtered through a 0.1 μm fluoropolymer filter to prepare resist lower film formation compositions (AL-1 to 52, comparative AL-1 to 8), respectively, and visual confirmation that no solids were present in each solution. Comparative AL-8 was prepared according to Example 34 described in Patent Document 7

[0221] . In Tables 3 and 4, the amount of each compound is by mass.

[0347] [Chemistry 53]

[0348]

[0349] [Table 3]

[0350]

[0351] [Table 4]

[0352]

[0353] [Example 1] Evaluation of storage stability (Examples 1-1 to 1-52, Comparative Examples 1-1 to 1-8)

[0354] The prepared resist lower film formation compositions (AL-1~52, comparative AL-1~8) were placed in brown bottles and sealed, and stored in a constant temperature incubator at -10°C for one month. Afterwards, the presence of precipitates in the solution was visually confirmed. The results are shown in Tables 5 and 6.

[0355] [Table 5]

[0356]

[0357] [Table 6]

[0358]

[0359] As shown in Tables 5 and 6, no precipitates were formed in Examples 1-1 to 1-52 and Comparative Examples 1-1 to 1-2, 1-4 to 1-5, and 1-7 to 1-8, in which the resist underlayer film forming composition (AL-1 to 52) of the present invention was used. It is believed that these materials contain at least one anion, and no new ion pairs are formed after mixing the materials, which is effective in suppressing the formation of precipitates. On the other hand, even if there is only one anion, precipitate formation was found in comparative examples where a polymer compound with a dangling onionized cationic structure was not used, i.e., comparative examples 1-3 where an organic sulfonyl anion was bonded to the polymer backbone, and comparative examples 1-6 where the hot acid generator contained an anionic molecule different from the polymer compound.

[0360] [Example 2] Solvent resistance evaluation (Examples 2-1 to 2-52, Comparative Examples 2-1 to 2-6)

[0361] The resist lower film forming compositions (AL-1~52, comparative AL-1, 2, 4, 5, 7, 8) prepared above were coated on a silicon substrate. After calcination at 215°C for 60 seconds, the film thickness was measured. PGMEA solvent was then dropped onto the substrate, and the substrate was left to stand for 30 seconds for rotary drying. The substrate was then baked at 100°C for 60 seconds to evaporate the PGMEA solvent. The film thickness was measured again, and the solvent resistance was evaluated by calculating the difference in film thickness before and after PGMEA treatment. The results are shown in Tables 7 and 8.

[0362] [Table 7]

[0363]

[0364] [Table 8]

[0365]

[0366] As shown in Tables 7 and 8, residual films were also observed after PGMEA treatment in the resist lower film formation compositions (AL-1 to 52) and comparative examples AL-1, 2, 4, 5, 7, and 8 of the present invention, confirming their curability. However, in comparative examples 2-4 to 2-6, which do not contain a hot acid generator, the film loss was slightly greater compared to other examples and comparative examples. This demonstrates that the curability of the film can be improved by adding a hot acid generator.

[0367] [Example 3] EUV exposure pattern formation test 1 using positive resist (Examples 3-1~3-45, Comparative Examples 3-1~3-6)

[0368] On a silicon wafer substrate, a spin-on carbon ODL-301 (88% by mass) manufactured by Shin-Etsu Chemical Industries, Ltd. is coated and baked at 350°C for 60 seconds to form an organic film with a thickness of 100 nm. A silicon-containing spin-on hard mask SHB-A940 (43% by mass) manufactured by Shin-Etsu Chemical Industries, Ltd. is then coated on top and baked at 215°C for 60 seconds to form a silicon-containing photoresist intermediate film with a thickness of 15 nm. Furthermore, the aforementioned photoresist underlayer film forming compositions (AL-1, 5~16, 18, 20, 21, 23~34, 36~52, comparative AL-1, 2, 4, 5, 7, 8) are coated and baked at 215°C for 60 seconds to form a photoresist underlayer film. The positive resist upper layer film composition described in Table 9 is coated on it, and baked at 100°C for 60 seconds to form a resist upper layer film with a thickness of 40 nm.

[0369] Regarding the composition for forming the upper layer of positive resist (single-layer resist for EUV), it is prepared by dissolving the polymer compound PRP1 and quencher Q1 in the proportions shown in Table 9 in an organic solvent containing 0.1% by mass of FC-4430 (manufactured by Sumitomo 3M Co., Ltd.), and filtering it through a 0.1 μm fluororesin filter.

[0370] [Table 9]

[0371]

[0372] Polymer compound: PRP1

[0373] Molecular weight: Mw=9,200

[0374] Dispersion: Mw / Mn = 1.8

[0375] [Chemistry 54]

[0376]

[0377] Quenching agent: Q1

[0378] [Chemistry 55]

[0379]

[0380] Then, the 18 nm line-to-space (LS) 1:1 pattern was exposed using an EUV exposure apparatus (ASML EUV scanning exposure machine NXE3400, NA 0.33, σ 0.9, 90-degree dipole illumination). It was then baked at 90°C (PEB) for 60 seconds and developed with a 2.38% (w / w) tetramethylammonium hydroxide (TMAH) aqueous solution for 30 seconds, resulting in a line-to-space pattern with a spacing width of 18 nm and a pitch of 36 nm. This pattern was then used as the object for cross-sectional observation using an electron microscope.

[0381] The cross-sectional shape of the obtained pattern was evaluated using an electron microscope (S-4700) manufactured by Hitachi, Ltd. The results are shown in Tables 10 and 11.

[0382] [Table 10]

[0383]

[0384] [Table 11]

[0385]

[0386] As shown in Tables 10 and 11, vertical cross-sectional pattern shapes were obtained in Examples 3-1 to 3-45 using the composition for forming the resist underlayer film of the present invention and Comparative Examples 3-4 to 3-6 using polymer compounds having an organic sulfonyl anionic structure. On the other hand, tailing shapes were observed in Comparative Examples 3-1 to 3-3 using polymer compounds without an organic sulfonyl anionic structure. It is believed that by providing an acid-generating structure to the polymer compound with a high content, acid can be supplied from the resist underlayer film at the bottom of the pattern, thus improving the tailing shape.

[0387] [Example 4] EUV exposure pattern formation test 2 using positive resist (Examples 4-1 to 4-45, Comparative Examples 4-1 to 4-6)

[0388] On a silicon wafer substrate, a spin-coating carbon ODL-301 (88% by mass) manufactured by Shin-Etsu Chemical Industries, Ltd. is coated and baked at 350°C for 60 seconds to form an organic film with a thickness of 100 nm. A silicon-containing spin-coating hard mask SHB-A940 (43% by mass) manufactured by Shin-Etsu Chemical Industries, Ltd. is then coated on top and baked at 215°C for 60 seconds to form a silicon-containing photoresist intermediate film with a thickness of 15 nm. Furthermore, the aforementioned photoresist underlayer film forming compositions (AL-1, 5~16, 18, 20, 21, 23~34, 36~52, comparative AL-1, 2, 4, 5, 7, 8) are coated and baked at 215°C for 60 seconds to form a photoresist underlayer film. The positive resist upper layer film-2 described in Table 12 is coated on it and baked at 105°C for 60 seconds to form a resist upper layer film with a thickness of 50 nm.

[0389] Regarding the positive resist upper film-forming composition-2 (EUV single-layer resist-2), it is prepared by dissolving the polymer compound PRP2, the hot acid generator PAG2, and the quencher Q2 in the proportions shown in Table 12 in an organic solvent containing 0.01% by mass of PF636 (manufactured by OMNOVA), and filtering it through a 0.1 μm fluororesin filter.

[0390] [Table 12]

[0391]

[0392] Polymer compound: PRP2

[0393] Molecular weight: Mw=5,200

[0394] Dispersion: Mw / Mn = 1.45

[0395] [Chemistry 56]

[0396]

[0397] Hot acid generator: PAG2

[0398] [Chemistry 57]

[0399]

[0400] Quenching agent: Q2

[0401] [Chem.58]

[0402]

[0403] Then, the aforementioned resist film was exposed using an ASML EUV scanning exposure machine NXE3400 (NA 0.33, σ 0.9 / 0.6, quadrupole illumination, mask with a hole pattern of 40 nm pitch and +20% offset on the wafer). PEB was applied at 80°C for 60 seconds on a heated plate, followed by development with a 2.38% (w / w) TMAH aqueous solution for 30 seconds, forming a hole pattern of 20 nm in size. This pattern was then used as the object, and its cross-sectional shape was observed using an electron microscope (S-4700) manufactured by Hitachi, Ltd. The results are shown in Tables 13 and 14.

[0404] [Table 13]

[0405]

[0406] [Table 14]

[0407]

[0408] As shown in Tables 13 and 14, Examples 4-1 to 4-45, which use the resist underlayer film formation composition of the present invention, have better cross-sectional shapes compared to Comparative Examples 4-1 to 4-6. On the other hand, in this test, Comparative Examples AL-5, 7, and 8, which showed good pattern shapes in Example 3, exhibited slight tailing shapes compared to the examples. Since these samples showed slightly greater film loss in the solvent resistance test, it is believed that insufficient curing led to mixing with other resists, resulting in slight tailing shapes.

[0409] [Example 5] Electron Beam Pattern Formation Experiment (Examples 5-1 to 5-33, Comparative Examples 5-1 to 5-3)

[0410] On a silicon wafer substrate, the above-mentioned components for forming a lower resist film (AL-10~16, 18, 19, 23, 24, 28~31, 33~40, 43~52, comparative AL-5, 7, 8) are coated and baked at 215°C for 60 seconds to form a lower resist film with a thickness of 5 nm. On the lower resist film, a metal-containing resist of an upper resist film material is coated and baked at 100°C for 60 seconds to form an upper resist film with a thickness of 40 nm.

[0411] Regarding the upper film material of the resist (containing metal resist), the resist material is mixed and dissolved according to the composition shown in Table 15 below, and the resulting solution is filtered through a 0.2 μm Teflon (registered trademark) filter to prepare resist composition R-1.

[0412] [Table 15]

[0413]

[0414] Synthesis of tin compound M-1 (component A)

[0415] [Chemistry 59]

[0416]

[0417] A mixture of 1.6 g of dibenzyltin oxide, 1.5 g of dimethyl carbonate, 1.1 g of methanol, and 60 g of toluene was stirred at 110 °C for 3 hours, then filtered at room temperature to remove insoluble components, followed by concentration under reduced pressure. Toluene was added to the concentrated residue and heated to dissolve it, then recrystallized and purified at room temperature to obtain 0.9 g of the target tin compound M-1 (55% yield).

[0418] Then, exposure was performed using an ELIONIX EB patterning apparatus (ELS-F125, accelerating voltage 125kV), with PEB applied at 150°C for 60 seconds on a heated plate, followed by development with 2-heptanone for 30 seconds to form a pattern.

[0419] The cross-sectional shape of the obtained pattern was evaluated using an electron microscope (S-4700) manufactured by Hitachi, Ltd., and the pattern roughness was evaluated using an electron microscope (CG5000) manufactured by Hitachi Advanced Technology, Ltd. The results are shown in Tables 16 and 17.

[0420] [Table 16]

[0421]

[0422] [Table 17]

[0423]

[0424] The meanings of the symbols in Tables 16 and 17 are as follows.

[0425] ◎: No residual film was found at the gap.

[0426] ○: Almost no residual film was found in the gap area.

[0427] △: Residual film was found in the gap.

[0428] As shown in Tables 16 and 17, in the tests using metal-containing resists, vertically shaped patterns were obtained in all examples and comparative examples. However, in Examples 5-29, which used structural units containing one hydroxyl group on each adjacent carbon atom, some residual films were observed at the spacing. If a coordinating substituent is placed on the adjacent carbon atom, it results in a strong interaction with the metal atoms in the metal-containing resist, potentially promoting residual film growth. Furthermore, in Comparative Examples 5-1 to 5-3, residual films were found at the spacing. This is believed to be due to the weak curing properties of the film, similar to that in Example 4, resulting in slight mixing.

[0429] Based on the above, if it is the composition for forming the resist underlayer film of the present invention, no precipitates will be produced even after long-term storage, and it exhibits excellent storage stability. At the same time, it can form a resist underlayer film with good pattern collapse suppression performance and the ability to remove resist residues at the bottom of the pattern. Therefore, it is extremely useful as a composition for forming the resist underlayer film used in multilayer resist methods. Furthermore, if it is the pattern forming method of the present invention using this composition, fine patterns can be formed with high precision on the processed substrate.

[0430] This specification contains the following specifications.

[0431] [1]: A composition for forming a resist underlayer film, characterized in that it comprises:

[0432] (A) A polymeric compound comprising structural units containing an organic sulfonyl anionic structure and an onium cationic structure from a sulfur atom, wherein the aforementioned onium cationic structure is dangling bonded to the polymer backbone;

[0433] (B) Thermal acid generating agents; and

[0434] (C) Organic solvents,

[0435] Furthermore, the aforementioned (A) polymeric compound and the aforementioned (B) thermal acid generating agent have the same organic sulfonyl anionic molecule.

[0436] [2]: The composition for forming the lower layer film of the resist as described in [1] above, wherein the structural unit containing the aforementioned organic sulfonyl anionic structure and the onium cation structure from sulfur atom contained in the aforementioned (A) polymer compound is represented by the following general formula (1) or (2).

[0437] [Transformation 60]

[0438]

[0439] (In the formula, R1 is a hydrogen atom or a methyl group, R2 is a substituted or unsubstituted divalent organic group or a single bond that may also contain ether or ester bonds, Ar1 and Ar2 are substituted or unsubstituted aromatic ring structures, Ar3 is a substituted or unsubstituted divalent aromatic ring structure, L1 is a divalent organic group or a single bond with 1 to 30 carbon atoms, X1 is a substituted or unsubstituted nitrogen atom or carbon atom, ether bond, ester bond, thioether bond, or single bond, X...) - It has the same structure as the organic sulfonyl anion molecule contained in the aforementioned (B) hot acid generating agent. Furthermore, R2, Ar1, and Ar2 can also form ring structures.

[0440] [3]: As described in [2] above, the composition for forming the lower layer film of the resist, wherein the aforementioned X - It has an alicyclic structure.

[0441] [4]: The composition for forming a resist underlayer film as described in any of [1] to [3] above, wherein the aforementioned polymer compound (A) does not contain a structural unit that satisfies the following condition:

[0442] In a structure other than the acrylate group and methacrylate group which function as polymerizable groups, there are a total of two or more nitrogen atoms, oxygen atoms or sulfur atoms with unpaired electrons, and there are two or fewer atoms between the aforementioned two nitrogen atoms, oxygen atoms or sulfur atoms.

[0443] [5]: The composition for forming a resist underlayer film as described in any of [1] to [4] above, wherein the ratio of the structural units containing an organic sulfonyl anion structure and an onium cation structure from sulfur atoms in the aforementioned (A) polymer compound is 1 mol% or more and 30 mol% or less.

[0444] [6]: A composition for forming a resist underlayer film as described in any of [1] to [5] above, wherein the aforementioned (A) polymer compound has at least one structural unit represented by the following general formula (3).

[0445] [Chemistry 61]

[0446] (3)

[0447] (In the formula, R3 is a hydrogen atom or a methyl group, and R4 is a group selected from formulas (3-1) to (3-3) below.)

[0448] [Chemistry 62]

[0449]

[0450] (3-1) (3-2) (3-3)

[0451] (In the formula, dashed lines represent atomic bonds.)

[0452] [7]: A composition for forming a resist underlayer film as described in any of [1] to [6] above, wherein the weight-average molecular weight of the aforementioned (A) polymer compound is 1,000 to 50,000.

[0453] [8]: The composition for forming a resist underlayer film as described in any of [1] to [7] above, wherein the aforementioned (C) organic solvent is a mixture of one or more organic solvents with a boiling point of less than 150°C and one or more organic solvents with a boiling point of 150°C or higher and a boiling point of less than 220°C.

[0454] [9]: The composition for forming a resist underlayer film as described in any of [1] to [8] above, wherein the composition for forming a resist underlayer film further contains at least one selected from (D) a surfactant and (E) a crosslinking agent.

[0455]

[10] : A pattern forming method, characterized by having the following steps:

[0456] (I-1) After coating a composition for forming a photoresist underlayer film as described in any one of [1] to [9] above onto a substrate to be processed, a photoresist underlayer film is formed by heat treatment.

[0457] (I-2) On the aforementioned lower resist film, a photoresist material is used to form an upper resist film;

[0458] (I-3) After pattern exposure of the aforementioned upper resist film, development is performed to form a pattern on the aforementioned upper resist film;

[0459] (I-4) Using the aforementioned patterned upper resist film as a mask, the pattern is transferred to the aforementioned lower resist film by dry etching; and

[0460] (I-5) Using the aforementioned resist film with the transferred pattern as a mask, the aforementioned substrate is processed to form a pattern on the aforementioned substrate.

[0461]

[11] : A pattern forming method, characterized by having the following steps:

[0462] (II-1) An organic film is formed on the substrate being processed;

[0463] (II-2) A silicon-containing photoresist intermediate film is formed on the aforementioned organic film;

[0464] (II-3) After coating the aforementioned silicon-containing photoresist intermediate film with a photoresist underlayer film composition as described in any one of [1] to [9] above, a photoresist underlayer film is formed by heat treatment.

[0465] (II-4) A photoresist material is used to form an upper resist film on the aforementioned lower resist film;

[0466] (II-5) After pattern exposure of the aforementioned upper resist film, development is performed to form a pattern on the aforementioned upper resist film;

[0467] (II-6) Using the patterned upper resist film as a mask, the pattern is transferred to the lower resist film by dry etching;

[0468] (II-7) Using the aforementioned patterned lower resist film as a mask, the pattern is transferred to the aforementioned silicon-containing intermediate resist film by dry etching.

[0469] (II-8) Using the aforementioned patterned silicon-containing resist interlayer as a mask, the pattern is transferred to the aforementioned organic film by dry etching; and

[0470] (II-9) Using the aforementioned organic film with the transferred pattern as a mask, the aforementioned substrate is processed to form a pattern on the aforementioned substrate.

[0471]

[12] : A pattern forming method, characterized by having the following steps:

[0472] (III-1) An organic film is formed on the substrate being processed;

[0473] (III-2) An inorganic hard mask intermediate film selected from silicon oxide film, silicon nitride film and silicon oxide nitride film is formed on the aforementioned organic film;

[0474] (III-3) After coating the aforementioned inorganic hard mask intermediate film with a composition for forming a photoresist underlayer film as described in any of [1] to [9] above, a photoresist underlayer film is formed by heat treatment.

[0475] (III-4) A photoresist material is used to form an upper resist film on the aforementioned lower resist film;

[0476] (III-5) After pattern exposure of the aforementioned upper resist film, development is performed to form a pattern on the aforementioned upper resist film;

[0477] (III-6) Using the patterned upper resist film as a mask, the pattern is transferred to the lower resist film by dry etching.

[0478] (III-7) Using the aforementioned patterned resist lower layer film as a mask, the pattern is transferred to the aforementioned inorganic hard mask intermediate film by dry etching.

[0479] (III-8) Using the aforementioned inorganic hard mask intermediate film with the transferred pattern as a mask, the pattern is transferred to the aforementioned organic film by dry etching; and

[0480] (III-9) Using the aforementioned organic film with the transferred pattern as a mask, the aforementioned substrate is processed to form a pattern on the aforementioned substrate.

[0481]

[13] : The pattern forming method described in

[12] above, wherein the aforementioned inorganic hard mask intermediate film is formed by using CVD or ALD.

[0482]

[14] : The pattern forming method of any one of

[10] to

[13] above, wherein the method of forming a pattern on the resist film above uses optical lithography, direct electron beam drawing, nanoimprinting, or a combination thereof with a wavelength of 10 nm or more and 300 nm or less.

[0483]

[15] : The pattern forming method of any one of

[10] to

[14] above, wherein a photoresist material comprising at least an organometallic compound and a solvent is used to form the aforementioned photoresist upper film.

[0484]

[16] : A pattern forming method as described in any of

[10] to

[15] above, wherein the developing method uses alkaline developing, developing with an organic solvent, or developing with dry etching.

[0485]

[17] : The pattern forming method of any one of

[10] to

[16] above, wherein the aforementioned processed substrate is formed by using a semiconductor device substrate, or by forming any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film on the semiconductor device substrate.

[0486]

[18] : The pattern forming method as described in

[17] above, wherein the aforementioned metal is silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or alloys thereof.

[0487]

[19] : A method for forming a photoresist underlayer film, used in a semiconductor device manufacturing step, characterized in that a photoresist underlayer film forming composition as described in any one of [1] to [9] above is spin-coated onto a substrate to be processed, and the substrate coated with the aforementioned photoresist underlayer film forming composition is heat-treated at a temperature of 100°C or higher and 300°C or lower for 10 to 600 seconds, thereby forming a photoresist underlayer film.

[0488]

[20] : A method for forming a photoresist underlayer film, used in a semiconductor device manufacturing step, characterized in that a photoresist underlayer film forming composition as described in any one of [1] to [9] above is spin-coated on a substrate to be processed, and the substrate coated with the aforementioned photoresist underlayer film forming composition is heat-treated in an environment with an oxygen concentration of 0.1% or more and 21% or less, thereby forming a photoresist underlayer film.

[0489]

[21] : A method for forming a photoresist underlayer film, used in a semiconductor device manufacturing step, characterized in that a photoresist underlayer film forming composition as described in any one of [1] to [9] above is spin-coated on a substrate to be processed, and the substrate coated with the aforementioned photoresist underlayer film forming composition is heat-treated in an environment with an oxygen concentration of 0.0001% or more and less than 0.1% to form a photoresist underlayer film.

[0490] Furthermore, this invention is not limited to the embodiments described above. The embodiments described above are examples, and those having a structure that is substantially the same as the technical concept described in the claims of this invention and performing the same effect are all intended to be included within the scope of this invention.

[0491] Explanation of reference numerals in the attached figures

[0492] 1:Substrate

[0493] 2: Processed layer

[0494] 2a: Pattern (the pattern formed on the processed layer)

[0495] 3: Organic membrane

[0496] 3a: Organic film pattern

[0497] 4: Silicon-containing intermediate film

[0498] 4a: Silicon-containing intermediate film pattern

[0499] 5: Underlying film of resist

[0500] 5a: Pattern of the underlayer resist film

[0501] 6: Top layer of resist film

[0502] 6a: Pattern of the upper layer of the resist film

[0503] 7: Exposure section

Claims

1. A composition for forming a resist underlayer film, characterized by comprising: (A) A polymeric compound comprising structural units containing an organic sulfonyl anionic structure and an onium cationic structure derived from a sulfur atom, wherein the onium cationic structure is dangling bonded to the polymer backbone; (B) Thermal acid generating agents; and (C) Organic solvents, Furthermore, the (A) polymer and the (B) hot acid generator have the same organic sulfonyl anion molecule.

2. The composition for forming a resist underlayer film according to claim 1, wherein, The structural unit containing the organic sulfonyl anion structure and the onium cation structure from the sulfur atom contained in the (A) polymer compound is represented by the following general formula (1) or (2); In the formula, R1 is a hydrogen atom or a methyl group; R2 is a substituted or unsubstituted divalent organic group or a single bond, which may also contain ether or ester bonds; Ar1 ​​and Ar2 are substituted or unsubstituted aromatic ring structures; Ar3 is a substituted or unsubstituted divalent aromatic ring structure; L1 is a divalent organic group or a single bond with 1 to 30 carbon atoms; X1 is a substituted or unsubstituted nitrogen atom or carbon atom, an ether bond, an ester bond, a thioether bond, or a single bond; X - It has the same structure as the organic sulfonyl anion molecule contained in the (B) hot acid generating agent; in addition, R2, Ar1 and Ar2 can also form ring structures respectively.

3. The composition for forming a resist underlayer film according to claim 2, wherein, The X - It has an alicyclic structure.

4. The composition for forming a resist underlayer film according to claim 1, wherein, The (A) polymer does not contain structural units that satisfy the following conditions: In a structure other than the acrylate group and methacrylate group which function as polymerizable groups, there are a total of two or more nitrogen atoms, oxygen atoms or sulfur atoms with unpaired electrons, and there are two or fewer atoms between the two nitrogen atoms, oxygen atoms or sulfur atoms.

5. The composition for forming a resist underlayer film according to claim 1, wherein, In the structural units of the (A) polymer compound, the ratio of the structural units containing an organic sulfonyl anionic structure and an onium cation structure from a sulfur atom is 1 mol% or more and 30 mol% or less.

6. The composition for forming a resist underlayer film according to claim 1, wherein, The (A) polymer has at least one structural unit represented by the following general formula (3); (3) In the formula, R3 is a hydrogen atom or a methyl group, and R4 is a group selected from formulas (3-1) to (3-3); (3-1)   (3-2)   (3-3) In the formula, the dashed lines represent atomic bonds.

7. The composition for forming a resist underlayer film according to claim 1, wherein, The weight-average molecular weight of the (A) polymer is 1,000 to 50,000.

8. The composition for forming a resist underlayer film according to claim 1, wherein, The organic solvent (C) is a mixture of one or more organic solvents with a boiling point of less than 150°C and one or more organic solvents with a boiling point of 150°C or higher and a boiling point of less than 220°C.

9. The composition for forming a resist underlayer film according to claim 1, wherein, The composition for forming the lower layer film of the resist also contains at least one selected from (D) surfactant and (E) crosslinking agent.

10. A pattern forming method, comprising the steps of forming a pattern on a substrate to be processed, characterized by the following steps: (I-1) After coating the composition for forming a photoresist underlayer film according to any one of claims 1 to 9 onto the substrate to be processed, a photoresist underlayer film is formed by heat treatment; (I-2) A photoresist material is used to form an upper resist film on the lower resist film; (I-3) After pattern exposure of the upper layer of the photoresist, development is performed to form a pattern on the upper layer of the photoresist; (I-4) Using the patterned upper resist film as a mask, the pattern is transferred to the lower resist film by dry etching; and (I-5) The patterned resist underlayer film is used as a mask to process the substrate and form a pattern on the substrate.

11. A pattern forming method, comprising the steps of forming a pattern on a substrate to be processed, characterized by the following steps: (II-1) An organic film is formed on the substrate being processed; (II-2) A silicon-containing photoresist interlayer is formed on the organic film; (II-3) After coating the silicon-containing photoresist intermediate film with the composition for forming a photoresist underlayer film according to any one of claims 1 to 9, a photoresist underlayer film is formed by heat treatment; (II-4) A photoresist material is used to form an upper resist film on the lower resist film; (II-5) After pattern exposure of the upper layer of the photoresist, development is performed to form a pattern on the upper layer of the photoresist; (II-6) Using the patterned upper resist film as a mask, the pattern is transferred to the lower resist film by dry etching; (II-7) Using the patterned lower resist film as a mask, the pattern is transferred to the silicon-containing intermediate resist film by dry etching. (II-8) Using the patterned silicon-containing resist interlayer as a mask, the pattern is transferred to the organic film by dry etching; and (II-9) Using the organic film with the transferred pattern as a mask, the substrate to be processed is processed to form a pattern on the substrate to be processed.

12. A pattern forming method, comprising the steps of forming a pattern on a substrate to be processed, characterized by the following steps: (III-1) An organic film is formed on the substrate being processed; (III-2) An inorganic hard mask intermediate film selected from silicon oxide film, silicon nitride film and silicon oxide nitride film is formed on the organic film; (III-3) After coating the composition for forming a photoresist underlayer film according to any one of claims 1 to 9 onto the inorganic hard mask intermediate film, a photoresist underlayer film is formed by heat treatment. (III-4) A photoresist material is used to form an upper resist film on the lower resist film; (III-5) After pattern exposure of the upper layer of the photoresist, development is performed to form a pattern on the upper layer of the photoresist; (III-6) Using the patterned upper resist film as a mask, the pattern is transferred to the lower resist film by dry etching; (III-7) The patterned resist lower layer film is used as a mask to transfer the pattern onto the inorganic hard mask intermediate film by dry etching. (III-8) Using the inorganic hard mask intermediate film with the transferred pattern as a mask, the pattern is transferred to the organic film by dry etching; and (III-9) Using the organic film with the transferred pattern as a mask, the substrate to be processed is processed to form a pattern on the substrate to be processed.

13. The pattern forming method according to claim 12, wherein, The inorganic hard mask intermediate film is formed using CVD or ALD methods.

14. The pattern forming method according to claim 10, wherein, The method of patterning the upper layer film of the resist uses optical lithography, direct electron beam drawing, nanoimprinting, or a combination thereof with wavelengths of 10 nm or more and 300 nm or less.

15. The pattern forming method according to claim 10, wherein, The upper layer of the photoresist is formed using a photoresist material containing at least an organometallic compound and a solvent.

16. The pattern forming method according to claim 10, wherein, The development methods include alkaline development, development using organic solvents, or development using dry etching.

17. The pattern forming method according to claim 10, wherein, The substrate being processed is made using a semiconductor device substrate, or by forming any one of a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film, and a metal oxide nitride film on the semiconductor device substrate.

18. The pattern forming method according to claim 17, wherein, The metal used is silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, cobalt, manganese, molybdenum, or alloys thereof.

19. A method for forming a photoresist underlayer film, used in a semiconductor device manufacturing step, characterized in that a photoresist underlayer film forming composition according to any one of claims 1 to 9 is spin-coated onto a substrate to be processed, and the substrate coated with the photoresist underlayer film forming composition is heat-treated at a temperature of 100°C or higher and 300°C or lower for 10 to 600 seconds, thereby forming the photoresist underlayer film.

20. A method for forming a photoresist underlayer film, used in a semiconductor device manufacturing step, characterized in that a photoresist underlayer film forming composition according to any one of claims 1 to 9 is spin-coated onto a substrate to be processed, and the substrate coated with the photoresist underlayer film forming composition is heat-treated in an environment with an oxygen concentration of 0.1% or more and 21% or less, thereby forming the photoresist underlayer film.

21. A method for forming a photoresist underlayer film, used in a semiconductor device manufacturing step, characterized in that a photoresist underlayer film forming composition according to any one of claims 1 to 9 is spin-coated onto a substrate to be processed, and the substrate coated with the photoresist underlayer film forming composition is heat-treated in an environment with an oxygen concentration of 0.0001% or more and less than 0.1% to form the photoresist underlayer film.

Citation Information

Patent Citations

  • Production of metal pipe coated with plastic

    JP1979015982A

  • Soft contact lens

    JP1982008521A

  • Liquid crystal display device

    JP1982008522A

  • Method and device for forming silicon nitride film, and method for preprocessing of cleaning thereof

    JP2002334869A

  • Polymer compound, resist material, and pattern-forming method

    JP2008111103A